Exposure assessment in industry specific retrospective occupational epidemiology studies. Issue 10 (October 1995) - Seixas, N S; Checkoway, H
Abstract : Quantitative estimation of exposure for occupational epidemiology studies has received increasing attention in recent years and, as a result, a body of methodological literature has begun to take form. This paper reviews the generic issues in the methodology of exposure assessment, particularly methods for quantitative retrospective assessment studies. A simple framework, termed an exposure data matrix (EDM), for defining and analysing exposure data is proposed and discussed in terms of the definition of matrix dimensions and scales. Several methods for estimation, interpolation, and extrapolation, ranging from subjective ratings to quantitative statistical modelling are presented and discussed. The various approaches to exposure assessment based on the EDM concept are illustrated with studies of lung disease among coal miners and other dust and chemically induced chronic occupational diseases. The advantages of validated statistical models are emphasised. The importance of analysis and control of errors in exposure assessments, and integration of the exposure assessment and exposure-response processes, especially for emerging occupational health issues, is emphasised.